No English in English Class: Improving Oral Production Through Project-Based Learning in a 7th Grade Class at the Institución Educativa Presbítero Bernardo Montoya (2016)
ABSTRACT: This study was designed to explore how oral production can be improved through Project-Based Learning. The participants were 38 students between twelve and thirteen years of age attending the seventh grade at I.E. Presbítero Bernardo Montoya. Data was collected through observations, surveys, recorded oral activities and participation charts. An initial review of the collected data revealed that there was no oral use of the target language during the classes. A five stage implementation, of PBL, was applied with varying results. I found that the main stage where students improved their oral production was during the scaffolding. It was here where they started to participate in the target language and even to make jokes.